2020
DOI: 10.1097/spv.0000000000000781
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Catheter Management Approaches Among Women Undergoing Benign Gynecologic Surgery: A Randomized Trial

Abstract: Objective The objective of this study was to identify differences in voiding trial success rates between delayed (postoperative day 1) and day of surgery catheter removal (“fast track”) among women undergoing benign gynecologic surgery. Rates of urinary tract infection, patient satisfaction, and lower urinary tract symptoms were compared between catheter management schemes. Methods Women undergoing benign gynecologic surgery were randomized to either “c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…En contexto de cirugía ambulatoria, el cateterismo intermitente es una alternativa razonable. En pacientes hospitalizados lo ideal es no sobrepasar las 24 h de SF [3], [11], [14], [15]. El uso de US puede ayudar a evaluar volúmenes sobre 600 ml y la necesidad de cateterismo.…”
Section: ¿Por Cuánto Tiempo Debe Mantenerse La Sf?unclassified
“…En contexto de cirugía ambulatoria, el cateterismo intermitente es una alternativa razonable. En pacientes hospitalizados lo ideal es no sobrepasar las 24 h de SF [3], [11], [14], [15]. El uso de US puede ayudar a evaluar volúmenes sobre 600 ml y la necesidad de cateterismo.…”
Section: ¿Por Cuánto Tiempo Debe Mantenerse La Sf?unclassified
“…The timing of catheter removal is the most important risk factor for urinary tract infections (UTIs) (Brackmann et al, 2020; Kranz et al, 2020; Umscheid et al, 2011) and immediate or early removal of catheters can not only reduce the risk of UTIs, but also improve patient comfort (Ahmed et al, 2014; Ellahi et al, 2021; Nicolle, 2014). Studies have shown that when urinary output must be monitored, Foley catheters can remain in situ for at least 24 hours after surgery, with no increase in rates of problems with voiding such as urinary retention, or bladder atony, and without increased risks of catheter-related adverse events, including UTIs (Chai & Pun, 2011; Lang et al, 2020). The use of catheters can also cause irritation of the urethra and urinary bladder, with resultant pain, and interference with ambulation (Ahmed et al, 2014; Liang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%